CORPORATE SOCIAL RESPONSIBILITY, GREEN ACCOUNTING AND EARNINGS MANAGEMENT: THE MODERATING ROLE OF GOOD CORPORATE GOVERNANCE - Mumpuni Wahyudiarti Sitoresmi; Agustina Prativi Nugraheni ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2026)
This study aims to analyze the effects of corporate social responsibility (CSR) disclosure and green accounting implementation on earnings management, with good corporate governance (GCG) as a moderating variable. Profitability, proxied by return on assets (ROA) and return on equity (ROE), serves as the control variable. The study adopts a quantitative method using secondary data. The population comprises consumer non-cyclical companies listed on the Indonesia Stock Exchange (IDX) over the 2019–2022 period. Purposive sampling yielded a final sample of 28 companies. A panel data regression model with Moderated Regression Analysis (MRA) was employed to analyze the data. The results show that CSR disclosure affects earnings management. In contrast, the implementation of green accounting does not affect earnings management, whereas profitability, proxied by ROA and ROE, positively affects earnings management. Good corporate governance is unable to moderate the effects of CSR disclosure and green accounting implementation on earnings management; however, it does moderate the effect of profitability on earnings management. Investors are therefore advised to rely on corporate governance mechanisms, particularly the proportion of independent commissioners, as a credible monitoring signal, since CSR disclosure and the implementation of green accounting have not been sufficient to curb earnings management practices in the absence of effective oversight.